Expert Answers

An illustration of the letter 'A' in a speech bubbles

ln e^(x+2) = 5 + ln e^2

We know that:

ln e^a = aln e = a*1 = a

==> ln e^(x+2) = 5 + ln e^2

==> (x+2) = 5 + 2

==> x+2 = 7

==> x= 7-2

==> x= 5

 

Approved by eNotes Editorial Team
Soaring plane image

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial